Deformation of the Femoropopliteal Segment: Effect of Stent Length, Location, Flexibility, and Curvature. (December 2016) - Ní Ghriallais, Ríona; Heraty, Kevin; Smouse, Bob; Burke, Martin; Gilson, Paul; Bruzzi, Mark
Purpose: To quantify the deformation behavior of the diseased femoropopliteal segment and assess the change to deformation behavior due to various stent placements.Methods: The length and curvature changes of 6 femoropopliteal segments (the right and left superficial femoral and popliteal arteries) from 3 cadavers were measured in 3-dimensional space based on rotational angiography image data in straight leg and flexed hip/knee (50°/90°) positions before and after placement of nitinol stents of varying type (EverFlex, Misago, and BioMimics 3D) and length (60, 100, and 200 mm) in different locations along the arteries. Three-dimensional centerline data were extracted for the measurements.Results: All 6 femoropopliteal cadaver segments displayed signs of peripheral artery disease. Hip/knee flexion resulted in vessel shortening and increases in the mean and maximum vessel curvatures in all cases. Location-specific results of the unstented arteries showed that magnitudes of vessel length and curvature change vary as a function of vessel length. The average shortening of the entire femoropopliteal segment due to flexion was observed at 10.7%±0.7%, which was reduced to 8.1%±0.9% after stent deployment. Average and maximum curvatures of the unstented segment increased due to flexion (average: 0.008±0.002 mm −1 to 0.019±0.006 mm −1, maximum: 0.030±0.009 mm −1 to 0.091±0.045 mm −1 ). After stent deployment, average and maximum curvatures of the flexed stented segments increased compared with the flexed unstented segments (average: 0.019±0.006 mm −1 to 0.022±0.004 mm −1, maximum: 0.091±0.045 mm −1 to 0.103±0.025 mm −1 ). The most flexurally stiff stent demonstrated the least ability to axially shorten during flexion of the leg at the knee joint.Conclusion: The deformation characteristics of the femoropopliteal segment change in the presence of a stent, with the change to the deformation behavior dependent on stent type, stent length, location, flexibility, and intrinsic centerline curvature.